Pengembangan Ekonomi Kreatif dari Bahan Limbah (Manik-Manik) melalui Platform Digital - Nurfaiza Nurfaiza; Tengku Bella Fazilah; Suci Afriana; Mira Hindriyani; Lisa Putri Sari Fatiha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the development process of a creative economy based on bead waste and the use of digital platforms as a marketing medium to increase product competitiveness. The background of the study is based on the phenomenon of increasing volumes of waste that have not been optimally managed and the low skills of business actors in utilizing digital technology. The research method used a qualitative approach with descriptive methods. Data were collected through in-depth interviews, participatory observation, documentation, and literature studies, with informants consisting of business actors, community leaders, representatives of relevant agencies, and consumers. The results of the study indicate that processing waste into beads not only reduces environmental impacts but also opens up creative business opportunities with high economic value. The use of digital platforms has proven effective in expanding market reach, improving branding, and driving sales, although there are still obstacles in the skills of digital entrepreneurs. This study recommends strengthening digital marketing capacity and ongoing mentoring for creative waste-based entrepreneurs to achieve economic and environmental sustainability. In addition, synergy between business actors, the government, and local communities is a crucial factor in supporting the development of a waste-based creative economy. The involvement of local governments through entrepreneurship training and facilitating access to technology is essential to address the challenge of limited digital capabilities of entrepreneurs. Local communities also play a role in maintaining sustainable production and encouraging innovation in bead designs based on local culture to add value and attract market share. This collaboration can create a conducive ecosystem for the growth of creative small and medium enterprises (SMEs), while strengthening local identity and increasing product competitiveness in national and global markets. Thus, developing a waste-based creative economy and utilizing digital marketing are relevant innovative strategies in addressing current economic and environmental challenges.